2003
DOI: 10.5194/hess-7-668-2003
|View full text |Cite
|
Sign up to set email alerts
|

Estimating rainfall distributions at high temporal resolutions using a multifractal model

Abstract: Rainfall data from 18 stations in the vicinity of Tokyo city, measured to a precision of 1 mm, were analysed for multifractal properties. A multifractal model based on the scaling properties of temporal distribution of rainfall intensities was formulated to investigate the intensity distribution relationships in the available scaling regime. Although conventional analysis did not provide encouraging results with these measurements, an alternative approach that could be applied to rainfall data of widely variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 17 publications
0
24
0
1
Order By: Relevance
“…As these inter-arrival times 710 F. Serinaldi: Modeling scaling and imperfect scaling in rainfall time series were longer than the typical evolution time of the storms for the specific climatic region (≈5-6 h on an average), a value of seven hours was adopted. This value is equal to or coherent with that applied by Salvadori and De Michele (2001) for a similar climate, and by Koutsoyiannis and Pachakis (1996) and Pathirana et al (2003) for different climates.…”
Section: Physical Propertiesmentioning
confidence: 76%
See 1 more Smart Citation
“…As these inter-arrival times 710 F. Serinaldi: Modeling scaling and imperfect scaling in rainfall time series were longer than the typical evolution time of the storms for the specific climatic region (≈5-6 h on an average), a value of seven hours was adopted. This value is equal to or coherent with that applied by Salvadori and De Michele (2001) for a similar climate, and by Koutsoyiannis and Pachakis (1996) and Pathirana et al (2003) for different climates.…”
Section: Physical Propertiesmentioning
confidence: 76%
“…The probability p 0 describes the lacunarity and is related to the fractal dimension of the series, whereas the distribution G of the positive weights is often assumed to be lognormal (e.g., Gupta and Waymire, 1993;Molnar and Burlando, 2005), log-Poisson (e.g., Deidda et al, 1999Deidda et al, , 2006Deidda, 2000;Onof et al, 2005;Sivakumar and Sharma, 2008;Mascaro et al, 2010) or logstable (e.g., Schertzer and Lovejoy, 1987;Olsson, 1995;Pathirana et al, 2003;Veneziano et al, 2006). It should be noted that the hypothesis of existence of a fractal support is alternative to the assumption of a low threshold for the measurable rainfall intensity, allowing for a cross-check of the two hypotheses.…”
Section: Discrete Beta-logstable (Bls) Canonical Modelmentioning
confidence: 99%
“…This approach is a standard tool for rainfall downscaling and has been applied by several authors. In particular, for rainfall time series, Güntner et al (2001) reproduced hourly rainfall from daily data sets concerning Brazil and the UK; Pathirana et al (2003) obtained hourly rainfall data from daily measurements for 18 stations close to Tokyo city, in Japan; Hingray and Ben Haha (2005) tested several disaggregation models, including random cascades, for the generation of 10-min rainfall time series from hourly rainfall heights observed at Pully, in Switzerland; Molnar and Burlando (2005) generated 10-min rainfall data referring to a raingauge located in Zurich, Switzerland; Paulson and Baxter (2007) generated a 10-s rainfall time series from lowerresolution data observed in the UK; Sivakumar and Sharma (2008) disaggregated daily time series into a 3-h data set; Rupp et al (2009) obtained hourly data from a daily set observed at the Christchurch Airport gauge in New Zealand; Licznar et al (2011) disaggregated quasi-daily rainfall data into 5-min time series for the raingauge located at Wroclaw, in Poland. An extensive theoretical review of the random cascade model is provided by Veneziano et al (2006b).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an area can be classified depending on the amount of precipitation it receives (Strahler and Strahler, 1978). Rainfall intensities increase in magnitude as the temporal accumulation length (time scale) decreases (Pathirana et al, 2003). This relation can be easily observed with the intensity-duration-frequency (IDF) curves, which are very useful for hydrology risk analysis and design (Eagleson, 1970;Chow et al, 1988;Veneziano and Furcolo, 2002;Veneziano et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%